The Psychological Unity of Pre - Islamic Poetry Text - Kadera, Ghithaa; Stite, Lara (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
The research in the literary work relationship in the inner world of the pre-Islamic poet is a sense of special emotion and embodies a unified feeling emanating from within the poetic text. Many Jahiliyya texts carry a psychological thread that combines them. , And this psychological unit draws its energy from the isotopes loaded with emotional signals that deepen the horizon of expectation, and make the receiver compatible with the poetic state of the creator of the text.